(NH4)2Ce(NO3)6/HNO3 as a High-Performance Oxidation Catalyst for the One-Step, Solvent-Free Synthesis of Dicyano Imidazoles. (19th August 2021) - Kalhor, Mehdi; Seyedzade, Zahra; Zarnegar, Zohre
Abstract: The first one-pot, solvent-free methodology for preparing 2-aryl-4, 5-dicarbonitrile imidazoles via the reaction of 2, 3-diaminomaleonitrile with aromatic aldehydes in the presence of cerium (IV) ammonium nitrate/nitric acid (CAN/NA) as a novel and high-performance oxidation catalyst is reported. The salient features of the described process in comparison with previous methods include one-step process, easy isolation of products, higher purity and yields, milder and cleaner conditions, short reaction time, and convenient manipulation.